LncRNA and mRNA expression characteristic and bioinformatic analysis in anemic diabetic foot ulcers - Lin, Jiayu; Wang, Jingying; Liang, Bo (Frontiers in Genetics, 2025)
BackgroundDiabetic foot ulcers (DFUs) are severe complications often accompanied by hemoglobin deficiency. While transcriptomic alterations are implicated in DFU pathogenesis, the roles of long non-coding RNAs (lncRNAs) in linking hemoglobin anomalies to iron-inflammatory dysregulation remain unclear.ObjectiveTo identify DFU-specific lncRNA-mRNA co-expression networks associated with iron metabolism and inflammation, and evaluate their diagnostic potential.MethodsRNA sequencing (Illumina NovaSeq 6000) was performed on skin tissues from 5 patients with type 2 diabetes and DFUs and 3 non-diabetic controls. Differentially expressed lncRNAs and mRNAs were identified using DESeq2. Functional pathway enrichment was assessed via Gene Set Enrichment Analysis (GSEA). Correlation networks integrating expression data were constructed to map lncRNA-mRNA interactions.ResultsAnalysis revealed 21 differentially expressed lncRNAs (1 upregulated, 20 downregulated) and 368 differentially expressed mRNAs (139 upregulated, 229 downregulated) in DFU tissues. GSEA confirmed significant enrichment of hemoglobin-related pathways, including iron uptake/transport, oxidative stress, and neutrophil degranulation. A co-expression network integrating these findings mapped interactions between 21 lncRNAs and 21 mRNAs. Key lncRNAs showed strong correlations with mRNAs involved in iron dysregulation and chronic inflammation, suggesting their contribution to DFU pathology.ConclusionOur analysis of anemia in DFU identifies distinct lncRNA-mRNA co-expression networks linked to hemoglobin deficiency. Key lncRNAs correlate strongly with mRNAs involved in perturbed iron handling and sustained inflammation. This suggests that dysregulation within these networks significantly contributes to the pathology of DFU with concurrent anemia, highlighting potential regulatory roles for these lncRNAs and offering avenues for diagnostic development.